Correlation Knowledge and Family Attitude with The Risk of Fall the Elderly in Barong Tongkok Health Center West Kutai - Agustina Telan (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Elderly or aging is a condition that occurs in human life. Aging is a lifelong process, not only starting from a certain time, but starting from the beginning of life. Growing old is a natural process, which means that a person has gone through three stages of life, namely children, adults and old both biologically and psychologically. Entering old age means experiencing various physical setbacks so that you experience the risk of falling. Methods: In this study, the research design used by the researcher was analytical research. Correlation analytic design with cross sectional approach with a total sample of 86 people. Results and Discussion: obtained p value 0.000 (<0.05) which means H1 is accepted and H0 is rejected, meaning that there is a relationship between knowledge and family attitudes with the risk of falling in the elderly at Barong Tongkok Health Center West Kutai in 2022. Conclusion: There is a relationship between knowledge and family attitudes with the risk of falling in the elderly at Barong Tongkok Health Center West Kutai in 2022